Superpower graphs of finite groups - Kumar A.; Selvaganesh L.; Cameron P.J.; Tamizh Chelvam T. (My University, 2025)
For a finite group G, the superpower graph S(G) of G is an undirected simple graph with vertex set G and two vertices are adjacent in S(G) if and only if the order of one divides the order of the other in G. The aim of this paper is to provide tight bounds for the vertex connectivity, discuss Hamiltonian-like properties of superpower graph of finite non-Abelian groups having an element of exponent order. We also give some general results about superpower graphs and their relation to other graphs such as the Gruenberg-Kegel graph. © 2025 World Scientific Publishing Company.